Crystal alignment of a LiFePO4 cathode material for lithium ion batteries using its magnetic properties. Issue 55 (8th October 2019) - Kim, Cham; Yang, Yeokyung; Ha, Dongwoo; Kim, Dong Hwan; Kim, Hoyoung
Abstract : The crystal orientation of LiFePO4 was controlled by using a magnetic field to facilitate favorable transport kinetics for lithium ions. Abstract : We suggest a way to control the crystal orientation of LiFePO4 using a magnetic field to obtain an advantageous structure for lithium ion conduction. We examined the magnetic properties of LiFePO4 such as magnetism and magnetic susceptibility, which are closely related to the crystal rotation in an external magnetic field, and considered how to use these properties for desired crystal orientation; thus, we successfully fabricated the crystal-aligned LiFePO4, in which the b -axis was highly aligned perpendicular to the surface of a current collector. Considering the low lithium ion conductivity of LiFePO4 inherently originated from its one-dimensional path for lithium ion diffusion, the crystal-aligned LiFePO4 potentially facilitates favorable transport kinetics for lithium ions during the charge/discharge process in lithium ion batteries. The crystal-aligned LiFePO4 should afford lower electrode polarization than pristine LiFePO4, and thus the former consistently exhibited higher reversible capacity than the latter.